Aqui a gente consegue juntar os nossos caquinhos: o coletivo de trabalho enquanto fonte de produção de recursos para a saúde de psicólogas de CRAS. - Nascimento, Iasmin Libalde (2017)
The present paper presents as a nodal proposal to investigate the relationship between the health-disease process and the existence of the professional gender among psychologists who work in basic social protection services in Social Assistance Referral Centers (CRAS). For that, three studies were carried out that were complemented in the task to discuss the work from different perspectives, collaborating to the understanding of the singularity of such object of study. Study 1 sought to draw a panorama of the academic production that discusses the performance of the psychologist in social assistance, focusing on CRAS, proposing to analyze, from the studies, the work activity of this professional in basic social protection and the reverberations of this work in the health of the psychologists who work in these spaces. Study 2 discussed the occupational health of the psychologist working at CRAS based on some of the characteristics of the work of these professionals, articulating the Karasek stress model and mental health (SRQ-20) and quality of life (WHOQOL- bref). A total of 53 psychologists working at CRAS in the state of Espírito Santo participated in this study. Study 3 discussed the relationship between the professional gender and the health / illness process experienced by psychologists who work in basic social protection. Divided into two moments, it initially analyzed the perception of the psychologists who work at CRAS in Vitória-ES about their work activity to later identify and analyze the professional gender of these technicians and their relationship with the health / disease process experienced by these workers. The results indicate that the panorama of the scientific literature referring to the period from 2007 to 2016 focuses on the following themes: Historical mapping / review, Psychologist practice discussion, Working conditions / difficulties and Proposed action. It suggests the need to invest in research and actions related to the health of the SUAS worker, still insufficiently investigated among these professionals. Regarding the labor aspects, the results show that the work of the psychologist in CRAS is characterized as active work, however a high level of mental illness and low quality of life among the participants was observed. It should be noted that the control dimension, in the labor context of the psychologist who works in basic social protection, does not seem to contribute positively to the health of the workers as predicted in the theoretical model. Finally, we can conclude from the reports of the participants of the third study that the experience of insecurity during the performance and the feeling of loss of professional identity suggests that the genre of psychologists of basic social protection is extremely weakened; which, together with the precariousness of work, produces professional ill health.